Evaluation of Safer House Roof Frame Models Using Coconut Wood Material - Don Kabo; Charles Sulangi (Formosa Journal of Sustainable Research, 2023)
The use of coconut wood is considered an environmentally friendly alternative because coconut wood comes from people's plantations without destroying forests. Another problem in the wooden house industry is knowing that the method of making roof frames is not yet a safe standard. The objectives of this research are: 1) Provide information about how to obtain conventional wood and coconut wood materials. 2) Explain how to select the quality and type of wood. 3) Explain that coconut wood can be used as a roof frame. 4) Explain the technical obstacles to roof trusses using coconut wood. 5) Explain the model for making a roof frame based on the basic requirements for a safer house. The method used in this research is descriptive qualitative through qualitative data analysis. The results of the roof frame model for the Woloan house do not meet the requirements for a house that is safer from earthquakes